IMPLEMENTASI PROGRAM KECAKAPAN KERJA (PKK) DI PUSAT KEGIATAN BELAJAR MASYARAKAT (PKBM) â€œBUGENVILâ€ BAGI WARGA BINAAN LEMBAGA PEMASYARAKATAN KELAS II KALIANDA KABUPATEN LAMPUNG SELATAN - Triyono Triyono; Rosidah Rosidah; Hinfa Mosshananza (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2022)
By-Law No. 12 of 1995 concerning Correctional Services, PKBM Bugenvil's Work Skills Program (PKK) was established. The purpose of this research is to describe the problem of the process of implementing the Work Skills Program (PKK) PKBM Bugenvil which is less than optimal and has an impact on the built citizens. The research method used is qualitative. The results of the research that the implementation of PKK in PKBM